Long-term inhibition of 5-alpha reductase and aromatase changes the cellular and extracellular compartments in gerbil ventral prostate at different postnatal ages - Corradi, Lara S.; Campos, Silvana G. P. [UNESP]; Santos, Fernanda C. A. [UNESP]; Vilamaior, Patricia S. L.; Goes, Rejane M. [UNESP]; Taboga, Sebastiao R. [UNESP] (Wiley-Blackwell Publishing, Inc, 2009)
As local steroid metabolism controls the bioavailability of active steroidal hormones in the prostate, the aim of this study, was to investigate the effects of absence of 5-alpha reductase (5 alpha-r) and aromatase (Aro) enzymes on prostatic cellular and extracellular components after long-term inhibition. Young, adult and old male Mongolian gerbils were treated orally, once a day, for 30 consecutive days, with Finasteride (10.0 mg/kg) and Letrozole (1.0 mg/kg) (5 alpha-r and Aro enzymes inhibitors respectively) simultaneously or separately. Animals were killed on 1, 7, 14 and 21 days post-treatment. Data obtained after double or single enzymatic inhibition with Finasteride and Letrozole demonstrated marked remodelling of epithelial and stromal compartments. During the post-treatment period, particularly on the first and the last analysed days, prostatic epithelial cells showed decreased cytoplasmic volume and secretory activity. In the stroma, collagen fibres had accumulated in the epithelial base and among smooth muscle cells, which showed reduced diameter and condensed cytoplasm, and some of them had a highly irregular external contour. Also in the sub-epithelial area, some fibroblasts acquired an activated phenotype besides increased deposits of amorphous granular material. In conclusion, the inhibition of 5 alpha-r and Aro enzymes affected, in a persistent manner, the structural and ultrastructural morphology of the prostate, irrespective of the gerbil's age. Hence these enzymes appear to be crucial in the maintenance of this gland during postnatal development. Also, these data bring more light to the complex issue of the mechanisms of local steroid metabolism and prostatic histology. Thus, the blockade of the steroid-metabolizing enzymes provided an important novel tool to study the relationship between sex steroids and normal physiology and diseases of the prostate.
Keywords: 5-alpha reductase; aromatase; epithelium; gerbil; stroma; Ventral prostate